Cost-effective energy and carbon emissions optimization in building renovation (annex 56): guidebook for professional home owners - Almeida, Manuela Guedes de (2017)
This guidebook is particularly intended for professional home-owners, i.e. individuals or companies that own and manage residential buildings. It is assumed that these owners are responsible for ensuring maintenance, repair and general servicing tasks and lead the decisions on the improvements to be made regarding comfort, safety, saving energy or just uplifting the buildings to contemporary needs or style. The main goal is to help in the decision-making process towards the optimized renovation of the residential building stock. More specifically, the guidebook provides a framework for the understanding of the relationships between cost-effective building renovation, energy savings and the use of renewable energy sources, highlighting the total added value achieved with the interventions.